1987
DOI: 10.1104/pp.84.2.404
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of 3-Hydroxy-3-Methylglutaryl Coenzyme A Reductase in the Regulation of Sesquiterpenoid Phytoalexin Synthesis in Potato

Abstract: The importance of 3-hydroxy-3-methylglutaryl coenzyme A reductase (HMG-CoA reductase) in the regulation of sesquiterpenoid phytoalexin accumulation in potato (Solanum tuberosum L. cv Kennebec) was examined. Wounding of potato tubers produced a large temporary increase in HMG-CoA reductase activity of the microsomal and organelle fractions. Treatment of wounded tuber tissue with the sesquiterpenoid phytoalexin elicitor arachidonic acid further increased and prolonged the HMG-CoA reductase activity in the micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
76
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(85 citation statements)
references
References 13 publications
9
76
0
Order By: Relevance
“…Yet, those studies were prompted, in part, by anticipating a corollary between the role HMGR plays in regulating isoprenoid metabolism in mammalian cells to that of plants. The current results, along with previous results showing the inhibition of sesquiterprenoid production by mevinolin (9, 19), indicate that, while HMGR activity is undoubtedly required for the synthesis of sesquiterpenoids, more stringent regulation occurs by a modulation of the branch point enzymes as well as by other means. In the present study, induction of HMGR activity was rapid and transient, and had returned to control levels by the time the sesquiterpenoid biosynthetic rate was maximum (6-9 h postelicitor addition).…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Yet, those studies were prompted, in part, by anticipating a corollary between the role HMGR plays in regulating isoprenoid metabolism in mammalian cells to that of plants. The current results, along with previous results showing the inhibition of sesquiterprenoid production by mevinolin (9, 19), indicate that, while HMGR activity is undoubtedly required for the synthesis of sesquiterpenoids, more stringent regulation occurs by a modulation of the branch point enzymes as well as by other means. In the present study, induction of HMGR activity was rapid and transient, and had returned to control levels by the time the sesquiterpenoid biosynthetic rate was maximum (6-9 h postelicitor addition).…”
Section: Discussionmentioning
confidence: 50%
“…We, like others (19,21), previously correlated the de novo synthesis of the sesquiterpenoids by elicitor-treated cells with a transient induction of HMGR activity (9). Yet, those studies were prompted, in part, by anticipating a corollary between the role HMGR plays in regulating isoprenoid metabolism in mammalian cells to that of plants.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these metabolic changes have been correlated with changes in HMGR activity (Stermer and Bostock, 1987;Chapell et al, 1991) or differential expression of specific HMGR genes (Stermer et al, 1991;Yang et al, 1991;Choi et al, 1992;Cramer et al, 1993). We showed that the Arabidopsis HMGP gene promoter is not induced in wounded leaves of transgenic tobacco plants containing construct (-857/+64)HMGP-GUS.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work by ourselves (9,31) and others (26,28) related the accumulation of sesquiterpenoids with the induction of 3-hydroxy-3-methylglutaryl CoA reductase, HMGR,3 a key regulatory step for isoprenoid metabolism in mammals (8). For example, addition offungal cell wall fragments to tobacco cell suspension cultures resulted in the de novo synthesis and accumulation ofextracellular sesquiterpenoids, including capsidiol (9).…”
mentioning
confidence: 99%